Optofluidic flow cytometer with in-plane spherical mirror for signals enhancement - Zorzi Filippo; Bonfadini Silvio; Aloisio Ludovico; Moschetta Matteo; Storti Filippo; Simoni Francesco; Lanzani Guglielmo; Criante Luigino (EPJ Web of Conferences, 2024)
Statistical analysis of properties of single microparticles, such as cells, bacteria or plastic slivers, has attracted increasing interest in recent years. In this field flow cytometry is considered the gold standard technique, but commercially available instruments are bulky, expensive, and not suitable for use in Point-of-Care (PoC) testing. Microfluidic flow cytometers, on the other hand, are small, cheap and can be used for on-site analysis. However, in order to detect small particles, they require complex geometries and the aid of external optical components. To overcome these limitations here we present an opto-fluidic flow cytometer with an integrated 3D in-plane spherical mirror for enhanced optical signal collection. As result the signal-to-noise ratio is increased by a factor of 6, enabling the detection of particle sizes down to 1.5μm. The proposed optofluidic detection scheme allows the simultaneous collection of particles fluorescence and scattering - using a single optical fiber - which is crucial to easily distinguish particle populations with different optical properties. The devices have been fully characterized using fluorescent polystyrene beads of different sizes. As a proof of concept for potential real-world applications, signals from fluorescent HEK cells and Escherichia coli bacteria were analyzed.